2020
DOI: 10.36846/cjafs.2020.22
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Micropropagation protocol for Lamium garganicum L. subsp. striatum (Sm.) Hayek var. striatum Grown Naturally in Turkey

Abstract: Lamiaceae family includes annual and perennial 250 genus which are commonly used for their medicinal aromatic properties due to its high biologically active compounds. Lamium garganicum L. subsp. striatum (Sm.) Hayek var. striatum (Telbalıcak) is a member of Lamium genus spread over in Turkey. Lamium species are used for cure since ancient times. Tissue culture provides important advantages for the conservation and sustainability of genetic resources such as clonal and mass production in a limited area. Microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Ozudogru et al (2011) [46] demonstrated that the medium supplemented with 4.65 µM Kin and 0.87 µM GA 3 ensured optimum shoot proliferation and maximum regeneration rate of Thymus longicaulis C.Presl and T. vulgaris L. vitroplants. Also, Sevindik and Tutuncu (2020) [47] showed that the combinations 8.88 µM BAP + 5.77 µM GA 3 and 8.88 µM BAP + 4.32 µM GA 3 are favorable for shoot multiplication of Lamium garganicum L. subsp. striatum (Sm.)…”
Section: Discussionmentioning
confidence: 99%
“…Ozudogru et al (2011) [46] demonstrated that the medium supplemented with 4.65 µM Kin and 0.87 µM GA 3 ensured optimum shoot proliferation and maximum regeneration rate of Thymus longicaulis C.Presl and T. vulgaris L. vitroplants. Also, Sevindik and Tutuncu (2020) [47] showed that the combinations 8.88 µM BAP + 5.77 µM GA 3 and 8.88 µM BAP + 4.32 µM GA 3 are favorable for shoot multiplication of Lamium garganicum L. subsp. striatum (Sm.)…”
Section: Discussionmentioning
confidence: 99%